Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) Terhadap Keaktifan Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas XI SMA Negeri 1 Pangaribuan Tahun Pembelajaran 2022/2023 - Nerya Sari Hayati Pakpahan; Ordekoria Saragih; Boho Pardede; Rida Gultom (Universitas Katolik Widya Karya Malang, 2023)
This research aims to find out whether the use of the Contextual Teaching and Learning (CTL) learning model can influence the active learning of Christian Religious Education and Character in class XI students at SMA Negeri 1 Pangaribuan for the 2022/2023 academic year. The method used in this research is quantitative with a descriptive inferential approach. The population is all class Data was collected using a positive closed questionnaire with 35 items. The results of data analysis show that there is a positive and significant influence of the Contextual Teaching and Learning (CTL) learning model on the active learning of Christian Religious Education and Character Education for class The positive relationship test obtained a value of rxy = 0.480 > rtabel(a=0,05,n=63)=0,244. b) Testing a significant relationship obtained a value of t = 4.271 > t table ttabel(a=0,05,dk=n-2=61)= 2,000. 2) Test the effect: a) Test the regression equation, obtained the regression equation Y ̂=